(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article the provisions of main normative-legal acts of the Republic of Kazakhstan on the issues of regulating investments, including foreign, are considered. Studying the works of Kazakhstan and foreign specialists on this topic author pays attention to the activity of the authorized bodies and organizations in the field of investment cooperation.